Factors affecting household debt to moneylenders - Mustika Mustika; Neneng Hasanah; Mohammad Iqbal Irfany (Annals of Human Resource Management Research, 2023)
Purpose: Moneylenders, sometimes called 'loan sharks' because of their high interest rates, are informal financial institutions that offer loans that are not in accordance with Islamic law. This study analyzes the factors that influence household behavior regarding debt to moneylenders. Research Methodology: This study employs descriptive and logistic regression analyses using primary data collected from locals in the Jagapura village, Cirebon. Results: The results indicate that basic household necessities determine debt behavior. However, Islamic financial literacy and increased income present effective solutions for moneylenders to overcome debt. Conclusions: This study finds that living necessities, Islamic financial literacy, and income significantly impact household debt to moneylenders. It recommends that Islamic financial institutions offer interest-free loans and collaborate with village governments to promote Sharia-compliant solutions. Limitations: This study is based on primary data from a specific village in Cirebon, Jagapura, which may not be representative of all households in debt to moneylenders in other regions or settings. Contributions: This study suggests that Islamic financial institutions should assist unbankable communities in need of funds for daily expenses by performing social functions, such as offering interest-free loans (qardhul hasan) and providing Islamic social finance. The establishment of sharia-compliant savings and loans could also be a solution to usury-related issues.